Implementasi Teknologi Informasi untuk Peningkatan Literasi Kesehatan di Loa Ulung, Tenggarong Seberang - Puspita Anggraini, Fitria Dewi; Zubaidah, Mona; Lumban Toruan, Vera Madonna; Fatmawati, Nur Khoma; Sholichin, Sholichin; Muniroh, Sifnie Sa’adatul (Universitas Pahlawan Tuanku Tambusai, 2025)
Information technology has become an important instrument in public health services, including in needs surveys and health education. This community service activity aims to implement Google Forms as a needs analysis survey tool and evaluate the effectiveness of adolescent reproductive health education in Loa Ulung Village, Kutai Kartanegara. The method used is community education with a pre-post test design approach using digital platforms. A needs survey was conducted on 46 adolescents aged 10-19 years using Google Forms to identify educational material priorities. Survey results showed four main priorities: smoking hazard socialization, adolescent reproductive health (HIV/AIDS), sexually transmitted infections, and mental health-substance abuse. Mental health education implementation showed score improvement from 6.70 to 7.04 (p=0.136), while HIV/AIDS education increased from 7.43 to 7.80 (p=0.155). Although the increase was not statistically significant, there was an improvement in adolescent knowledge. The educational game